2005
DOI: 10.1534/genetics.103.020842
|View full text |Cite
|
Sign up to set email alerts
|

Trans-splicing of the mod(mdg4) Complex Locus Is Conserved Between the Distantly Related Species Drosophila melanogaster and D. virilis

Abstract: The modifier of mdg4, mod(mdg4), locus in Drosophila melanogaster represents a new type of complex gene in which functional diversity is resolved by mRNA trans-splicing. A protein family of Ͼ30 transcriptional regulators, which are supposed to be involved in higher-order chromatin structure, is encoded by both DNA strands of this locus. Mutations in mod(mdg4) have been identified independently in a number of genetic screens involving position-effect variegation, modulation of chromatin insulators, apoptosis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Reverse transcription was performed using random primers and AMV reverse transcriptase (Roche). PCR was carried out using control primers for RP49 (Gabler et al, 2005): rp-49-F, TGTCCTTCCAGCTTCAAGATGACCATC and rp-49-R, CTTGGGCTTGCGCCATTTGTG. mcph1 primers were, exon 6: F, GCCATTAACCACAATAAGCCATCGG, and exon 8: R, CTCATAGGGCTCT -TCATTGATCC.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Reverse transcription was performed using random primers and AMV reverse transcriptase (Roche). PCR was carried out using control primers for RP49 (Gabler et al, 2005): rp-49-F, TGTCCTTCCAGCTTCAAGATGACCATC and rp-49-R, CTTGGGCTTGCGCCATTTGTG. mcph1 primers were, exon 6: F, GCCATTAACCACAATAAGCCATCGG, and exon 8: R, CTCATAGGGCTCT -TCATTGATCC.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Compared with cis-splicing, trans-splicing has been observed much less often in higher eukaryotes (McManus et al 2010;Zhang et al 2010). The best-characterized transspliced gene in higher eukaryotes is mod(mdg4) in Drosophila, which contains common 59 exons from one chromosomal locus and 31 alternative 39 exons from multiple loci, that are located on both DNA strands (Dorn and Krauss 2003;Gabler et al 2005;McManus et al 2010). It has been reported that the trans-splicing of mod(mdg4) is conserved in silkworm, based on evidence from one public EST sequence (Krauss and Dorn 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Trans-splicing is found less commonly in many higher eukaryotes, including in several chloroplast and mitochondria genes in plants (Koller et al 1987;Pereira de Souza et al 1991), in mod(mdg4) and lola in flies (Horiuchi et al 2003;Gabler et al 2005), and in numerous genes in mammals (Fujieda et al 1996;Hu et al 2013). Recently, deep sequencing has enhanced the identification of transsplicing events throughout the transcriptome (McManus et al 2010;Zhang et al 2010;Shao et al 2012).…”
mentioning
confidence: 99%
“…In mod(mdg4), alternative 3 ′ exons from multiple loci on both DNA strands are trans-spliced to a 5 ′ transcript containing four common exons (Fig. 1A) and result in at least 31 isoforms (Labrador et al 2001;Dorn and Krauss 2003;Gabler et al 2005;McManus et al 2010). Trans-splicing of mod(mdg4) is conserved in insects, including silkworms (Shao et al 2012), mosquitos (Krauss and Dorn 2004), and cotton bollworms (Cai et al 2012).…”
mentioning
confidence: 99%